Overview of behavioural study on human governance determinants in automotive sector - Malani, Manimaharan; Suhaidah, Hussain (Asian Scholars Network (ASNet), 2020)
Practices of governance play a significant role in attaining a high-quality workforce. Establishment of organizational governance has created a definition of human governance. Human governance is a critical factor for enhancing employee satisfaction and ethical conduct in the automotive service sector. The Malaysian automotive industry grew in terms of revenue, production, jobs and local content but failed to enforce honesty in the organization's employees. Corruption is one of the crucial problems in creating a responsible government, considering that it is an indicator that something has occurred in the organization's management. The best approach to addressing this problem is by combining the effort to curb corruption with consideration from the viewpoint of good governance. This paper suggested exploring the relationship between human governance and the risk of corruption. This paper would provide some insight into the effect that determinants of human governance are being used as elements that should lead to combating corruption in the automotive service sector.